Adaptability of breeds of rams and breed types of range ewes to market lamb production in Kansas - Menzies, C.S.; Holland, L.A.; John, R.E. (Kansas Agricultural Experiment Station, 2011)
Western ewes of the three predominant types (Texas ewes or finewools, Northwest blackface crossbreds, and Northwest whiteface crossbreds) commonly found in Kansas were obtained as ewe lambs in the fall of 1951 and bred to Hampshire, Suffolk, Shropshire, and Southdown rams for six seasons. A different set of rams has been used each year, and the ewes are rotated so that no ewes are bred to the same breed of ram each year. Wool and lamb production records have been kept on the different types of ewes, and lamb production figures have been obtained for the four sire groups
Keywords: Sheep; Rams; Ewes; Production